Implementing developmentally appropriate learning experiences for secondary school learners: the Zimbabwean case - Gudyanga, Anna; Gudyanga, Ephias (Journal of Research & Method in Education, 2016)
Teacher preparation emphasizes application of foundational issues anchored in psychological, sociological and philosophical underpinnings. With such knowledge, teachers are expected to effectively organise the learning experiences of children accordingly. This study, therefore, sought to find out to what extend in-service teachers were able to organise learning experiences that are developmentally appropriate. The mixed methods approach guided this study, as it was informed by both the positivist and interpretivist paradigms which acted as lenses through which we viewed this study. Questionnaires, interviews and class observations were the methods used as data collecting tools. Twenty participants (13 females, 7 males), were purposively selected from Gweru urban secondary schools of Zimbabwe. It was noted that teachers are not able to implement Developmentally Appropriate Practices (DAP) for various reasons ranging from heavy teaching loads, big classes, low teaching motivation, inadequate DAP knowledge among others. In the midst of other recommendations, it was highlighted that parents were to meaningfully interact with schools to bridge the gap between the home and the school, notwithstanding challenges facing the teacher which require the urgency which cannot be gainsaid.